Investigating the theory of environmental Kuznets curve on environmental quality index in Indonesia - Nurcahyo, Yanuar Bangun; Fatin, Sausan; Reza, Muhammad Fathur (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
The relationship between economy, environment, and human capital has developed into a discourse that has attracted the attention of all parties, especially academics. The inconsistency of research results that occur in developing and developed countries is our basis for conducting research with the hypotheses that have been built. This research aimed to determine the effect of human capital and gross domestic product on environmental quality in Indonesia. This study used panel data during the 2015-2020 period. The ordinary least square analysis measures the effect of the independent variables on the dependent one in the model. The results of this study indicate that human capital has a positive and significant impact on improving the quality of the environment. There are several aspects on which human capital can positively affect the environment, one of which is education. On the other hand, an increase in GDP has an inverse effect on the environment. This is because the economy's orientation in developing countries still focuses on the industrialization sector, which negatively impacts the environment. Moreover, this is reinforced by the low level of supervision carried out by the regional or central government.